Presenting a Hybrid Model of Digital Transformation Based on Artificial Intelligence and System Dynamics in E-businesses - Bejani, Rahim; Sanai, Mohammad Reza; Abbasi, Rezvan (Management Strategies and Engineering Sciences, 2026)
Digital transformation, as an undeniable necessity in the current era, plays a key role in the competitiveness and development of e-businesses. This research aims to design a hybrid digital transformation model combining Artificial Intelligence (AI) and System Dynamics (SD) to help companies like Digikala achieve sustainable competitive advantage by optimizing business processes, improving customer experience, and increasing organizational flexibility. This study is applied in terms of objective and descriptive-analytical in terms of method. Data were collected through interviews with Digikala experts, organizational document review, and examination of implemented AI systems. In the modeling phase, system dynamics was used to simulate the interaction of key digital transformation factors, and artificial intelligence (including machine learning and natural language processing) was used to analyze big data and predict market trends. The combination of these two methods allowed for the design of a dynamic and intelligent model. The implementation of the proposed model showed that integrating AI and system dynamics leads to improved strategic decision-making through more accurate demand forecasting and identification of customer behavioral patterns, reduced operational costs by using intelligent process automation, increased customer satisfaction due to personalized services and faster responsiveness, and higher flexibility in facing market changes by using scenario simulations. This model can be used as a framework for other e-businesses to accelerate digital transformation.